The Effect of Internal Barriers on the Connection Between Stakeholder Integration and Proactive Environmental Strategies - Delgado-Ceballos, Javier; Aragon-Correa, Juan Alberto; Ortiz-de-Mandojana, Natalia; Rueda-Manzanares, Antonio (2012)
This paper examines the influence of internal barriers on the relationship between the organizational capability of stakeholder integration and proactive environmental strategies. We adopt a moderate hierarchical regression model to test the hypotheses using data from a sample of 73 managers in the business education industry. The paper contributes to stakeholder theory by showing that stakeholder integration positively influences the development of proactive environmental strategies when managers perceive internal barriers to the development of such strategies. This article also explores an ethical dilemma—managers may use the stakeholder integration capability to support their own interests rather than to benefit stakeholders.
Keywords: Capability of stakeholder integration; Proactive environmental strategy; Natural Environment